Book review: Exploring decolonising themes in SA Sport History: Issues and challenges - Kaur, Tarminder (Southern Journal for Contemporary History, 2019)
Exploring decolonising themes in SA Sport History: Issues and challenges, Cleophas, Francois Johannes (ed.), Bloemfontein, African Sun Media, 2018. 154 pp, ISBN 978-1-928357-94-0